Analisis Kualitas Pelayanan Terhadap Kepuasan Konsumen Berbelanja Baju Polos dan Sablon Digital di Toko Cititex Cabang Kota Pematangsiantar - Chairani, Yulia; Suhada, Suhada; Hardinata, Jaya Tata (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The satisfaction of consumers shopping for plain clothes at the Cititex store in the Pematangsiantar branch is one of the most important things in assessing the level of service and quality provided by the store to its consumers. The purpose of this study was to determine the quality of service to consumers in terms of Quality (Quality), Responsiveness (Responsiveness), Empathy (Empathy) to consumers. At the Cititex plain clothes shop, the Pematangsian branch, these three aspects have not been measured with certainty, so the shop finds it difficult to determine which aspects should be improved. The method used in this study is the C4.5 Algorithm, where the data source used is a questionnaire technique given to consumers. The research test process uses RapidMiner software to create a decision tree. The results obtained 2 rules for the classification of the level of consumer satisfaction with the quality of materials and store service. The C4.5 algorithm can be used in the case of consumer satisfaction at the Cititex plain clothes shop, Pematangsiantar branch with an accuracy rate of 96.50%. From the results of the analysis is expected to improve the quality of materials and services in providing services to consumers to be even better